Dampak Penyalahggunaan Narkotika dan Obat Obatan Terlarang Di Masyarakat - Yusup Yusup; Resti Okta Sari (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
The impact of drug use is extremely harmful in the long run. In this regard, this article aims to reflect more deeply on the real impacts of drug use in our society. Through a better understanding of this issue, it is hoped that a stronger collective consciousness can be formed to face this challenge in a more effective and holistic way. The method used in this research is qualitative. The result is that drug use is not only an individual problem, but also a complex social problem that requires a holistic approach from various parties, including the government, health institutions, education, and society as a whole. Prevention, education, and access to adequate rehabilitation and health care services are key to addressing the negative impacts of drug use.